Guided Act and Feel Indonesia – Internet-based Behavioral Activation Intervention for Depression in Indonesia: A Systematic Cultural Adaptation - Arjadi, Retha; Nauta, Maaike H; Suryani, Angela O; Bockting, Claudi L. H. (UI Scholars Hub, 2018)
Depression is one of the leading causes of the global disease burden, affecting millions of people worldwide. The availability of mental health treatment, however, remains very limited in many low-middle income countries, including Indonesia. Internet-based interventions are known to have the potential to deliver mental health treatment economically and appropriately according to numerous studies conducted in high-income countries. In the current study, we describe a systematic cultural adaptation of an internet-based behavioral activation intervention for depression in Indonesia, named Guided Act and Feel Indonesia. During the adaptation, relevant stakeholders were involved, including licensed clinical psychologists, mental health communities, lay counselors, and patients. The adaptation used the formative method for adapting psychotherapy (FMAP) to adapt eight important cultural elements (language, persons, metaphors, content, concepts, goals, methods, and context). The intervention was adapted from the original Dutch version called Doe en Voel, consisting of 8 structured modules that are offered in a secure online environment. The adapted version is being delivered during an ongoing randomized controlled trial with non-face-to-face support from lay counselors who work under the supervision of licensed clinical psychologists. The challenges that were faced during the cultural adaptation are discussed.